Competitive Mooting as Clinical Legal Education: Can Real Benefits be Derived from an Unreal Experience? - Louise Parsons
Competitive mooting is very popular among Australian law schools and Australian law students perform very well in mooting competitions. This paper argues that competitive mooting, although it involves hypothetical scenarios and is often somewhat removed from what most legal practitioners will realistically be involved with in daily practice, nevertheless offers an invaluable educational experience at law school. Although competitive mooting does not fall within the narrow definition of clinical legal education (because of its lack of realism, and it being a simulation exercise), it nevertheless shares the benefits of experiential learning pedagogy with clinical legal education. In addition, the unique educational benefits produced by the intense and challenging experiences in competitive mooting accord well with the changing landscape of the legal profession, and the perceived shift in the role of a law degree, from a professional qualification to a valuable companion degree.